Whistleblowing as Planned Behavior – A Survey of South Korean Police Officers - Park, Heungsik (Journal of business ethics, 2009)
This article explores the relevance of the Theory of Planned Behavior to whistleblowing research, and considers whether its widely tested validity as a model of the link between attitudes, intention, and behavior might make it an appropriate candidate for a general theory to account for whistleblowing. This proposition is developed through an empirical test of the theory’s predictive validity for whistleblowing intentions. Using a sample of 296 Korean police officers, the analysis showed that attitude, subjective norm, and perceived behavioral control all had significantly positive main effects on internal whistleblowing intentions, but for external whistleblowing intentions only subjective norm was significant. The implications of these findings for applying the Theory of Planned Behavior to whistleblowing research are discussed.